Control and resilience: The importance of an internal focus to maintain resilience in academically able students. Issue 1 (2nd January 2017) - Kronborg, Leonie; Plunkett, Margaret; Gamble, Nicholas; Kaman, Yvette
ABSTRACT: This article reports one component of a longitudinal multilayered research project originating from a unique partnership between a university and a selective secondary school in Victoria, Australia. One hundred and twenty-five Year 10 academically able students at the school completed a survey at two different times to investigate a range of motivational constructs, including locus of control and resilience. Students were grouped according to their locus of control (LoC) focus (either internal or external), and, subsequently, scores from their resilience profiles were compared using multivariate analysis of variance. Findings illustrated that students with a more internally focused locus of control were more resilient at two time points. These findings have important implications for educators, as resilience is recognized as an important attribute to be developed in all students, including academically able students.